2020
DOI: 10.1088/2053-1591/ab95d9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-shelled Ni6MnO8 hollow microspheres for high-performance supercapacitors

Abstract: Binary transition metal oxides have attracted tremendous interest for their excellent redox activity and large natural abundance. They could achieve distinct electrochemical properties by engineering special hollow structures. In this work, we have synthesized triple-shelled Ni 6 MnO 8 hollow microspheres constructed with nanosheets through step by step adsorption of the corresponding metal ions on carbon spheres followed by calcination in air. The as-prepared Ni 6 MnO 8 hollow microspheres with nanosheet shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…6c ). 51 The fitting of Mo 3d spectrum of Ni x Mo 1− x O y revealed two spin–orbit doublets, characteristic of Mo 5+ and Mo 6+ ( Fig. 6d ).…”
Section: Resultsmentioning
confidence: 92%
“…6c ). 51 The fitting of Mo 3d spectrum of Ni x Mo 1− x O y revealed two spin–orbit doublets, characteristic of Mo 5+ and Mo 6+ ( Fig. 6d ).…”
Section: Resultsmentioning
confidence: 92%
“…[76] Previous work has shown that Ni(OH) 2 can also partially convert into NiO upon repetitive cycling in the OER region. [77] TEM characterisation of the electrode after cycling (Figure S8) demonstrated that the crystalline state was maintained with lattice spacings of 0.20 and 0.22 nm that corresponds to the (012) and (100) crystal planes of NiO , [78,79] and CoO, [80] respectively. For NMC 811 a similar trend was observed, however there are additional contributions after cycling, in particular at 855.6 eV which indicates the possible formation of some Ni 3 + species (NiOOH), [81] which is typically observed when Ni 2 + precursors are used as OER electrocatalysts.…”
Section: Resultsmentioning
confidence: 99%